2008
DOI: 10.1016/j.ymgme.2008.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Residual levels of tripeptidyl-peptidase I activity dramatically ameliorate disease in late-infantile neuronal ceroid lipofuscinosis

Abstract: Classical late-infantile neuronal ceroid lipofuscinosis (LINCL) is a hereditary neurodegenerative disease of childhood that is caused by mutations in the gene (CLN2) encoding the lysosomal protease tripeptidyl-peptidase I (TPPI). LINCL is fatal and there is no treatment of demonstrated efficacy in affected children but preclinical studies with AAV-mediated gene therapy have demonstrated promise in a mouse model. Here, we have generated mouse CLN2 mutants that express different amounts of TPPI activity to bench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 27 publications
(38 reference statements)
3
39
0
Order By: Relevance
“…Given that individuals carrying this mutation demonstrate a milder, protracted course of the disease in comparison with the classic phenotype [Wisniewski et al, 1999], our data suggest that even a very low level of TPPI activity is able to slow down the disease process. In agreement with these data obtained for human TPPI, mice homozygous toward the Arg446 mutation (an equivalent of human Arg447) also reveal a distinctly milder phenotype than animals with disruption of TPPI [Sleat et al, 2008]. According to our findings, low-temperature treatment significantly increased the levels of the proenzyme and the mature polypeptide of p.Arg447His mutant protein (by approximately five-fold).…”
Section: Discussionsupporting
confidence: 91%
“…Given that individuals carrying this mutation demonstrate a milder, protracted course of the disease in comparison with the classic phenotype [Wisniewski et al, 1999], our data suggest that even a very low level of TPPI activity is able to slow down the disease process. In agreement with these data obtained for human TPPI, mice homozygous toward the Arg446 mutation (an equivalent of human Arg447) also reveal a distinctly milder phenotype than animals with disruption of TPPI [Sleat et al, 2008]. According to our findings, low-temperature treatment significantly increased the levels of the proenzyme and the mature polypeptide of p.Arg447His mutant protein (by approximately five-fold).…”
Section: Discussionsupporting
confidence: 91%
“…WES by NGS was performed, allowing the identification of one common mutation in TPP1 (intron 5-c.509-1G>C) and a novel mutation, exon 8-p.Glu343Asp (KS, Boston). However, on looking at the published cases, it appears that some of the SCAR7 individuals also showed very low levels of leukocyte activity; and 4) variations in TPP1 activities correlated with variant phenotypes in CLN2 knock out mice [95]. CLN3 disease, juvenile: This is the second most frequent NCL type [6], with 6 identified patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is in agreement with Van Diggelen et al [6] reporting an abrogated TPP1 enzyme activity in fibroblasts of late-infantile NCL patients, and variable residual activity in leucocytes. Studies on a CNL mouse model confirm this observation having shown that compound heterozygous mice for the R447H change and a null allele, exhibit residual TPP1 activity, and manifest delayed disease onset and longer survival [19]. The nature of this residual activity in leucocytes is unclear, it could be hypothesized that it is, at least, partially influenced by the presence of other peptidases.…”
Section: Discussionmentioning
confidence: 82%
“…Both variants had previously been associated with CLN2 [18] and were predicted to dramatically affect protein function stability. In particular, arginine 447 is highly conserved among orthologs, and the Arg-to-His substitution was previously documented to result in a less stable or active enzyme [19]. Sanger sequencing validated both variants, and provided evidence for the shared compound heterozygosity in the three siblings, and the heterozygous state of the unaffected parents for either lesion.…”
Section: Wes Analysis Variant Detection and Validationmentioning
confidence: 84%